Postharvest Quality of Cut Zinnia Flowers Cultivated Under Different Irrigation Levels and Growing Seasons - Martins, Rosária da Costa Faria; Pêgo, Rogério Gomes; Cruz, Eleandro Silva da; Bueno, Mateus Marques; Carvalho, Daniel Fonseca de (Journal of Agricultural Studies, 2021)
The quality of floral stems depends on a set of pre-harvest factors which can influence their postharvest longevity. Although the identification of visual signs of senescence through scales is decisive in assessing the loss of floral quality in the postharvest period, this scale does not exist for zinnia flowers (Zinnia elegans Jacq.). Thus, the objectives of this study were to evaluate the effect of different irrigation levels and growing seasons on the postharvest longevity of zinnia floral stems; and to determine a senescence scale to assess their durability. Therefore, zinnia plants (cv. “Red California Giant”) were cultivated in pots inside a greenhouse in Seropédica (Rio de Janeiro, Brazil), with a randomized block design, under four irrigation levels (46%, 64%, 75% and 100% of the species’ water requirement) and two cycles (autumn-winter and winter-spring). At the end of each cycle, 48 stems from each treatment were harvested and placed in containers holding 300 mL of supply water. For all irrigation levels and crop cycles, there was an increase in the fresh stem weight on the first days after harvesting and the water absorption rate was higher on the first day of evaluation. The proposed senescence scale allowed us to evaluate the loss of floral quality in the postharvest period. The stems from both cycles had satisfactory results, mainly of commercial longevity and the score 5 on the scale, which represents 100% of the stems’ market value. The main postharvest results of the zinnia floral stems were not influenced by the irrigation levels.